Sobre el "Itinerario de la armada" y el descubrimiento de México. Los impresos de la relación de la expedición de Grijalva - Jiménez del Campo, Paloma (El Colegio de México, 2015)
Not enough importance has been lent to the fact that news of discovery of Mexico was divulged by the European press which followed the story of Juan de Grijalva’s expedition, as told by the chaplain of the fleet, Juan Díaz. The present article centers its attention both on the moment in which this text was written and on the circumstances of its diffusion. In this way we hope to explain why the text was silenced in Spain and why, on the other hand, it became widely known in Italy. The article throws new light on this chronicle in particular and on the diffusion of the news of the New Word in general.